A taxonomic catalogue of the Dyspnoi Hansen and Sørensen, 1904 (Arachnida: Opiliones) - Schönhofer, Axel L. (Zootaxa, 2013)
An update of the systematics and determination key of the Opiliones suborder Dyspnoi is provided. The included cata-logue represents the first comprehensive species and synonymy listing since Roewer (1923). It summarises all taxonomic changes to date and attempts to be a sound basis against the exponential growing number of online errors, for which ex-amples are given. Species taxonomy features most obvious changes within the Nemastomatidae. The number of species in the collective genus Nemastoma is reduced from 96 (Hallan 2005) to its sensu stricto definition of 7, and the excluded names are transferred to other genera or considered as nomina dubia, predominantly in Paranemastoma. The systematics of the superfamily Ischyropsalidoidea is discussed and family-level diagnoses are renewed to support taxonomical chang-es: The morphological heterogeneity in the Sabaconidae is resolved by reverting the family to its original monogeneric state. Taracus and Hesperonemastoma are separated as Taracidae fam. n., and Crosbycus is tentatively transferred to this assembly. The remaining genera of Ceratolasmatidae, Acuclavella and Ceratolasma, are included as subfamily Ceratolas-matinae in the Ischyropsalididae and Ischyropsalis is assigned subfamily status, respectively. Other nomenclatural acts are restricted to species-group level with the following synonymies established: Sabacon jonesi Goodnight & Goodnight, 1942 syn. n. (=cavicolens (Packard, 1884)), Dicranolasma diomedeum Kulczyński, 1907 syn. n. (=hirtum Loman, 1894), Mitostoma (Mitostoma) sketi Hadži, 1973a syn. n. (=chrysomelas (Hermann, 1804)), Mitostoma asturicum Roewer, 1951 syn. n. (=pyrenaeum (Simon, 1879a)), Nemastoma formosum Roewer, 1951 syn. n. (=Nemastomella bacillifera bacillif-era (Simon, 1879a)), Nemastoma reimoseri Roewer, 1951 syn. n. (=Paranemastoma bicuspidatum (C.L. Koch, 1835)), Nemastoma tunetanum Roewer, 1951 syn. n. (=Paranemastoma bureschi (Roewer, 1926)), Phalangium flavimanum C.L. Koch, 1835 syn. n. (=Paranemastoma quadripunctatum (Perty, 1833)), Crosbycus graecus Giltay, 1932 syn. n. (=Parane-mastoma simplex (Giltay, 1932)), Nemastoma bimaculosum Roewer 1951 syn. n. (=Paranemastoma titaniacum (Roewer, 1914)), Trogulocratus tunetanus Roewer, 1950 syn. n. (=Calathocratus africanus (Lucas, 1849)), Trogulus albicerus Sø-rensen, 1873 syn. n. (=Calathocratus sinuosus (Sørensen, 1873)), Metopoctea exarata Simon, 1879a syn. n. (=Trogulus aquaticus Simon, 1879a), Trogulus galasensis Avram, 1971 syn. n. (=Trogulus nepaeformis (Scopoli, 1763)) and Trogulus roeweri Avram, 1971 syn. n. (=Trogulus nepaeformis (Scopoli, 1763)). Paranemastoma werneri (Kulczyński, 1903) is elevated from subspecies to species. Ischyropsalis luteipes Simon, 1872b is proposed as nomen protectum, taking pre-cedence over Lhermia spinipes Lucas 1866 nomen oblitum. The same accounts for Anelasmocephalus cambridgei (West-wood, 1874) nomen protectum, taking precedence over Trogulus violaceus Gervais, 1844 nomen oblitum, Trogulus closanicus Avram, 1971 nomen protectum over Trogulus asperatus C.L. Koch, 1839a nomen oblitum, as well as Trogu-lus martensi Chemini, 1983 nomen protectum over Trogulus tuberculatus Canestrini, 1874 nomen oblitum. New com-binations, all from Nemastoma, are Histricostoma anatolicum (Roewer, 1962), Mediostoma globuliferum (L. Koch, 1867), Nemastomella hankiewiczii (Kulczyński, 1909), Nemastomella maarebense (Simon, 1913), Nemastomella monchiquense (Kraus, 1961) and Paranemastoma simplex (Giltay, 1932); from Mitostoma: Nemastomella armatissima (Roewer, 1962). Revived combinations are Nemastomella cristinae (Rambla, 1969) (from Nemastoma) and Nemastomella sexmucronatum (Simon, 1911) (from Nemastoma). The following Nemastoma are transferred to Paranemastoma but suggested as nomina dubia: aeginum (Roewer, 1951), amuelleri (Roewer, 1951), bolei (Hadži, 1973a), caporiaccoi (Roewer, 1951), carneluttii (Hadži, 1973a), ferkeri (Roewer, 1951), gigas montenegrinum (Nosek, 1904), gostivarense (Hadži, 1973a), ikarium (Roewer, 1951), quadripunctatum ios (Roewer, 1917), kaestneri (Roewer, 1951), longipalpatum (Roewer, 1951), mace-donicum (Hadži, 1973a), multisignatum (Hadži, 1973a), nigrum (Hadži, 1973a), perfugium (Roewer, 1951), santorinum (Roewer, 1951), senussium (Roewer, 1951), sketi (Hadži, 1973a), spinosulum (L. Koch, 1869). Further suggested nomina dubia are Trogulus coreiformis C.L. Koch, 1839a, Trogulus lygaeiformis C.L. Koch, 1839a and Trogulus templetonii West-wood, 1833.